Patients report inferior quality of care for knee osteoarthritis prior to assessment for knee replacement surgery – a cross-sectional study of 517 patients in Denmark - Ingelsrud, Lina H; Roos, Ewa M; Gromov, Kirill; Jensen , Sofie S; Troelsen, Anders (Acta Orthopaedica, 2019)
Background and purpose — Clinical care pathways for knee osteoarthritis (OA) are not always in line with clinical guidelines. We investigated (1) the patient-perceived quality of OA management, (2) which physiotherapist-delivered treatments patients with knee OA have attempted, and (3) patients’ expected subsequent treatment, at the time of referral to an orthopedic surgeon. Patients and methods — This cross-sectional study included all patients with scheduled first-time appointments for knee OA at an orthopedic outpatient clinic from April 2017 to February 2018. Postal questionnaires included the 16-item OsteoArthritis Quality Indicator (OA-QI) questionnaire and questions about physiotherapist-delivered treatment for knee OA. Results — 517 of 627 (82%) eligible patients responded. Responders’ (63% female) mean age was 67 years. The mean pass rate for the 16 independent quality indicators was 32% (8–74%). Sub-grouped into 4 categories, pass rates for independent quality indicators ranged from 16–52% regarding information, 9–50% regarding pain and functional assessment, 8–35% regarding referrals, and 16–74% regarding pharmacological treatment. While half of responders felt informed of physical activity benefits, only one-third had consulted a physiotherapist during the past year. Commonest physiotherapist-delivered treatments were exercise therapy for 22% and participation in the Good Life with osteoArthritis in Denmark (GLA:D) program for12% of responding patients. 65% expected surgery as subsequent treatment. Interpretation — Patients with knee OA are undertreated in primary care in Denmark; however, our findings may only reflect healthcare settings that are comparably organized. Our results call for better structure and uniform pathways for primary care knee OA treatment before referral to an orthopedic surgeon.